Forest School Movement For Developing Social Skill, Gross Motor Skill, And Fine Motor Skill In TK XYZ Bintaro - Yuliana Yuliana; Agus Santoso (CV. Syntax Corporation Indonesia, 2022)
The Covid-19 pandemic has forced a change in the way children learn at school. It has been almost two years since they were forced to do learning from home by using some media, such as: Zoom, and Google Meets. However, after the children were vaccinated, some schools have been allowed to hold face-to-face meetings. Since then, the results of the reflections of several teachers have revealed that there is a decline in the children's social skills, gross motor skills, and fine motor skills. One approach that fits the school environment and curriculum at the XYZ Kindergarten is the Forest School Movement, which is an approach to teaching and learning by doing some natural activities that stimulate the children. The research design used was the Classroom Action Research (CAR) consisting of two cycles, with 20 children aged 3-4 years as the subjects and using a rubric for the assessment, together with the observation techniques to triangulate the data. The data were also supported by the interviews from the four teachers. The results have indicated that after the two cicles of the interventions given, there is a 24,64% increase of the social skills, a 33,75% increase of the gross motor skills and a 31,67% increase of the fine motor skills